2018
DOI: 10.2147/cia.s157507
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between enteral nutrition and serum levels of inflammatory factors and cardiac function in elderly patients with heart failure

Abstract: ObjectiveTo investigate enteral nutrition’s effect on serum inflammatory factors and the cardiac function of malnourished elderly patients with heart failure.Patients and methodsA total of 105 elderly patients with heart failure were randomly divided into 3 groups: Treatment Group A, Treatment Group B, and the Control Group (Group C), each group having 35 patients and being administered conventional heart failure treatment. Group A was treated with 500 mL·d−1 of enteral nutrition for 1 month. Group B was given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…After the administration of a high-caloric (600 kcal), high-protein (20 g), and oral nutritional supplement for 6 weeks to cachexic heart failure patients, significant improvements were observed in the quality of life, 6-m walking test, and tumor necrosis factor-α without the significant recovery of peak VO 2 or the left ventricular ejection fraction; BNP was not measured in that study [21]. After the administration of 500 mL/day of enteral nutrition for 3 months to elderly heart failure patients, marked improvements were noted in BNP, interleukin-6, tumor necrosis factor-α, and C-reactive protein levels [22]. After adjustments for transthyretin levels, the risk associated with BNP ≥ 500 pg/mL was no longer significant.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…After the administration of a high-caloric (600 kcal), high-protein (20 g), and oral nutritional supplement for 6 weeks to cachexic heart failure patients, significant improvements were observed in the quality of life, 6-m walking test, and tumor necrosis factor-α without the significant recovery of peak VO 2 or the left ventricular ejection fraction; BNP was not measured in that study [21]. After the administration of 500 mL/day of enteral nutrition for 3 months to elderly heart failure patients, marked improvements were noted in BNP, interleukin-6, tumor necrosis factor-α, and C-reactive protein levels [22]. After adjustments for transthyretin levels, the risk associated with BNP ≥ 500 pg/mL was no longer significant.…”
Section: Discussionmentioning
confidence: 73%
“…After adjustments for transthyretin levels, the risk associated with BNP ≥ 500 pg/mL was no longer significant. Transthyretin is an important indicator of not only the nutritional status, but also the survival of hemodialysis patients after adjustments for age, gender, race, hemodialysis vintage, the diabetic state, and nutritional markers, including serum albumin levels [22,23]. A recent study reported that serum transthyretin levels correlated with body fat mass [24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that anthropometric indicators are a measure of muscle mass, 12,13 and muscle mass is associated with exercise tolerance [3][4][5] in patients with CHF. However, the direct association between anthropometric indicators and exercise tolerance in CHF has not been investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several previous studies have used mid-arm muscle circumference (MAMC) as an indicator of nutritional status and muscle mass in patients with CHF. 13,14 Anthropometric indicators are advantageous for assessment, as they are easily evaluable in routine clinical practice with no associated costs. However, to our knowledge, the association between anthropometric indicators and exercise tolerance in patients with CHF has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The longer the treatment time, the greater the improvement in cardiac function and inflammatory factors. 61 Use of PN is safe and well tolerated during the perioperative period in patients with heart failure who are treated with ventricular assistance devices. 62 …”
Section: Nutritional Support Treatment Of Common Diseases Among the Elderlymentioning
confidence: 99%